Internalization of Religious Character in Biology Learning (Case Study at SMPIT Qurratta A'yun Ponorogo) - Damayanti, Herli; Nuraini; Saputro, Anip Dwi (Journal of Educational Technology and Instruction, 2023)
Researchers conduct research in SMPIT Qurrata A’yun Ponorogo, a civilization school that combines sciences and Islamic religion with a school model that is able to integrate qouli knowledge and kauni become one unit in learning. This study uses a qualitative approach, a case study type and data collection techniques through interviews, observation and documentation. Data analysis used descriptive techniques by using data reduction flow, presentation, and conclusion. The results of the study at SMP IT Quratta A’yun Ponorogo show that religious character values are internalized through religious activities and self-development through tahfidz Qur'an, and other religious activities. The steps used in internalizing religious characters in biology learning have three stages, namely: the value transformation stage, the value transaction stage, transinternalization of values. It is expected that biology teachers will always maximize their learning activities by inserting the Al-Qur'an and Hadith in the biology learning process.